RELATIONSHIP OF POST TRAUMATIC GROWTH PSYCHOLOGICAL DISTRESS AND QUALITY OF LIFE AMONG RENAL FALIURE PATIENTS - Ehsan, Neelam; ., Nayab; Khan, Adam; Shahid, Amna Khan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the relationship and impact of post traumatic growth and psychological distress on quality of life among renal failure patients seeking dialysis, and to see differences in these variables among different age group patients. Study Design: Cross sectional study. Place and Duration of Study: Lady Reading Hospital, Peshawar, Government Hospital Mardan Pakistan, from Jan to Jun 2019. Methodology: A sample of 300 renal failure Patients 18 years or older who had a diagnosis of end-stage renal disease receiving treatment within different dialysis units were approached through purposive sampling technique. Post traumatic growth inventory Quality of life scale and the Psychological distress scale were used to measure the study variables. Results: Results reveal that psychological distress has a negative correlation with post traumatic growth (r=- 0.77**, p<0.01) and Quality of Life (r= -0.73**, p<.01). Whereas, Post Traumatic Growth has a strong positive correlation with Quality of Life (r=0.68*, p<0.01). Similarly, Psychological distress (β= -0.89, p<.000) and post traumatic growth (β=0.25, p<.000) significantly predict quality of life and explained 57% variance (F (2,297) = 198.4, p<0.000, R2=0.57) among the sample. Moreover, the results also show significant differences in the study variables between the two age groups (i.e., 16 to 32 years and 33 to 48 years) and it further suggest that middle age patients had higher levels of PTG as compared to younger and older patients. Conclusion: This study reveals a significant negative relationship of post traumatic growth with psychological distress and a significant effect of post traumatic growth and psychological distress on the quality of life in the sample. This study also concludes that middle-age group patients had higher levels of post traumatic growth as compared to young and old patients.